2000
DOI: 10.4315/0362-028x-63.8.1087
|View full text |Cite
|
Sign up to set email alerts
|

Acidified Sodium Chlorite Antimicrobial Treatment of Broiler Carcasses

Abstract: An acidified sodium chlorite (ASC) solution was investigated for its antimicrobial effects on broiler carcasses processed under conditions similar to those used in U.S. commercial poultry facilities. Of particular interest was the ability of the ASC solution to reduce natural bioburden in a prechill procedure. A number of parameters such as pretreatment washing of carcasses with water (no wash versus water wash), ASC concentration (500, 850, and 1,200 ppm), method of application (spray versus dip), and method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 16 publications
3
38
0
1
Order By: Relevance
“…These reductions were mainly obtained for naturally contaminated poultry carcasses and parts. Increasing the ASC concentration in the immersion solution from 500 ppm to 1200 ppm increased the reductions of coliforms by 1.1 log CFU ml À1 , whereas the results of aerobic bacteria or E. coli were hardly influenced (Kemp, Aldrich, & Waldroup, 2000). Comparison of ASC immersion and spray treatment in the study of Sinhamahapatra et al (2004) showed that immersion yielded slightly higher reductions (0.3 log CFU cm À2 ) for aerobic bacteria and coliforms than spraying.…”
Section: Acidified Sodium Chloritementioning
confidence: 93%
“…These reductions were mainly obtained for naturally contaminated poultry carcasses and parts. Increasing the ASC concentration in the immersion solution from 500 ppm to 1200 ppm increased the reductions of coliforms by 1.1 log CFU ml À1 , whereas the results of aerobic bacteria or E. coli were hardly influenced (Kemp, Aldrich, & Waldroup, 2000). Comparison of ASC immersion and spray treatment in the study of Sinhamahapatra et al (2004) showed that immersion yielded slightly higher reductions (0.3 log CFU cm À2 ) for aerobic bacteria and coliforms than spraying.…”
Section: Acidified Sodium Chloritementioning
confidence: 93%
“…These findings indicated that HClO 2 was the active species governing the inactivation of V. parahaemolyticus. It is believed that the strong antimicrobial activity of the electrically neutral undissociated form of the oxychloro compounds, such as HClO and HClO 2 , can be attributed to its ability to penetrate into the microbial cell across the cell membrane, i.e., the lipid bilayer Fukuzaki, 2006;Horiguchi et al, 2015;Kemp, 2000 . Consequently, HClO 2 can attack cellular components inside the cell, thereby giving a strong antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, pH control is one strategy to increase the antimicrobial activity of NaClO 2 . Acidification of NaClO 2 solutions produces chlorous acid HClO 2 , and this acid is capable of penetrating the bacterial membrane, and exerts its bactericidal effect by affecting protein functions inside cells Kemp et al, 2000 . However, HClO 2 is rapidly converted to chlorine dioxide ClO 2 under strong acidic conditions as in ASC Gordon et al, 1972 ; thus ClO 2 is considered to be a principle component of the strong antimicrobial activity observed for ASC.…”
Section: Discussionmentioning
confidence: 99%